Effects of size and allocation method on stock portfolio performance: a simulation study - Ng, K.Y.; Goh, K.L. (2011)
This paper examines the performance of portfolios of stocks listed in the Malaysian exchange through a simulation study. The effects of different portfolio sizes and fund allocation methods on return per unit of risk, or risk reward, were analyzed. Risk rewards increase with the inclusion of a larger number of stocks in a portfolio but at a decreasing rate. The results show that a portfolio size of 11 stocks is generally sufficient to generate reasonable risk rewards. The results, confirmed by holdout validation, also suggest that the conditional optimal and minimized variance allocation methods yield high risk reward, while the equal weight method has the poorest performance.